Armed Conflicts and Effective Curriculum Delivery: Perspectives of Basic Education Teachers in Nigeria - Elyakubu, L. I.; Ikpe, I. D. (Journal of Research in Adult and Continuing Education, 2024)
This study determined the effects of armed conflict on effective delivery of Basic education curriculum in schools in affected areas in Nigeria. The study adopted descriptive survey design. Two research questions were formulated to guide the study. A researcher-made questionnaire was used to elicit information from respondents. The population of the study consisted of 50 teachers. A sample of 30 teachers representing 60% of the entire population was selected through simple random sampling technique with non-replacement balloting technique. Instrument for data collection was a 10 item structured questionnaire of four point Likert scale of Very high extent, High extent, Low extent and Very low extent respectively. A reliability coefficient of 0.81 was obtained for the instrument using Pearson’s Product Moment Correlation (PPMC) Statistics. The result revealed that numerous armed conflict activities militated against effective basic education curriculum delivery in Nigeria. The identified challenges have drastic effects on curriculum delivery in basic education. Based on the findings, several recommendations were made. Specifically the urgent need for good security to safe guard curriculum delivery in basic education which is the foundation of all levels of education in Nigeria was emphasized.
Keywords: Armed conflict; curriculum delivery; basic education; teachers; Nigeria